Purwarupa Sistem Monitoring dan Otomatisasi Air Limbah Industri Tekstil dengan Metode Fuzzy Logic Mamdani - Imam Pratama Setiady; Mochammad Hannats Hanafi Ichsan; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Textile industry is one of national mainstay sectors that contribute significantly to economic progress. High production in textile industry causes damage to environmental because production process produces wastewater which is dumped into river areas. Report from Badan Pusat Statistik (BPS) that quality of river water in Indonesia is in not-good category. To overcome these problems, required systems can carry out monitoring of classification status of wastewater and automation actions. This research implements DS18B20 sensor, pH sensor and turbidity sensor as an input monitoring process controlled by Arduino Mega 2560. Classification and automation process is applied to fuzzy logic Mamdani method for making wastewater status and automation of speed on DC motor R385. Fuzzy logic Mamdani method is applied using fuzzy system designer LabVIEW toolkit to implementation of the fuzzification, inference and defuzzification. All of processes displayed real-time in LabVIEW with form of numbers, indicators and graphs from both the monitoring and fuzzy logic Mamdani results. Accuracy fuzzy logic Mamdani method in system was comparing with system in MATLAB. Results MAPE for water status is 0.49%, disposal is 0.49% and water reservoir is 0.50%. It very good results.